First Record of Cyphonotus testaceus (Pallas, 1781) (Coleoptera: Scarabaeidae: Melolonthinae: Melolonthini) from Pakistan - Ahmed, Zubair; Bezdek, Ale; Akhter, Muhammad Atique (Biological Sciences - PJSIR, 2014)